(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2018)
India has more than 100 million internet users out of which one half opt for online purchases and the number is rising sharply every year. The growth in the number of online shoppers is greater than the growth in Internet users, indicating that more Internet users are becoming comfortable to shop online. The capability of purchasing without leaving your place is of great interest to many consumers. Not only does online shopping offer really good deals, but also brings optimum convenience to the consumers. Moreover, the use of Internet tools for price searching and comparison provides an additional advantage in consumers’ final decision, as they can purchase their desired products in the lowest available price. This paper focuses on the understanding of demographic profiles of adopters and non-adopters of online shopping. For this purpose the data from 400 respondents was collected in the form of questionnaires. The study has been conducted in 3 cities of Punjab, a sample of urban respondents were selected from the Jalandhar, Ludhiana and Amritsar The paper also analyses the various reasons for adoption and non-adoption of online shopping.